2018
DOI: 10.1101/272690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A catalog of microbial genes from the bovine rumen unveils a specialized and diverse biomass-degrading environment

Abstract: BackgroundThe rumen microbiota provides essential services to its host and, through its role in ruminant production, contributes to human nutrition and food security. A thorough knowledge of the genetic potential of rumen microbes will provide opportunities for improving the sustainability of ruminant production systems. The availability of gene reference catalogs from gut microbiomes has advanced the understanding of the role of the microbiota in health and disease in humans and other mammals. In this work, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 56 publications
2
17
0
1
Order By: Relevance
“…In capybara gut CAZymes arsenal, invertases from GH32 family were identi ed in a proportion of approx. 1.5%, which is similar to that reported for several gut microbiomes from ruminants to humans (30,31). It is worth to mention that in the sequenced genome of capybara itself there is no gene encoding GH32 invertases, which holds for all mammals sequenced to date.…”
Section: Capybara Gut Microbiome Strategies For the Breakdown Of Dietsupporting
confidence: 83%
See 1 more Smart Citation
“…In capybara gut CAZymes arsenal, invertases from GH32 family were identi ed in a proportion of approx. 1.5%, which is similar to that reported for several gut microbiomes from ruminants to humans (30,31). It is worth to mention that in the sequenced genome of capybara itself there is no gene encoding GH32 invertases, which holds for all mammals sequenced to date.…”
Section: Capybara Gut Microbiome Strategies For the Breakdown Of Dietsupporting
confidence: 83%
“…These enzymes are often associated with the later steps in the degradation cascade of several plant polysaccharides such as cellulose, heteroxylans, mixed-linkage β-glucans and β-mannans. Moreover, it has already been reported that these families are highly abundant in several host-associated gut microbiomes such as human, mouse, swine, and cattle rumen (30), probably due to their broad functions.…”
Section: Capybara Gut Microbiome Strategies For the Breakdown Of Dietmentioning
confidence: 99%
“…36 and their abundance is highly related to high-fiber long-term diets 37,38 . Their presence in fecal microbiota is highly reported in human 39 and other animals such as ruminants, predominating in rumen microbiota [40][41][42] .…”
Section: Discussionmentioning
confidence: 98%
“…gnPULs are generally identified in Bacteroidetes genomes by the presence of an adjacent susC and susD homologue pair (Terrapon et al, 2015;Wu et al, 2015;Svartström et al, 2017;Wong et al, 2017;Terrapon et al, 2018;Lapébie et al, 2019;Patnode et al, 2019;Li et al, 2020), which encodes a core TonB-dependent transporter (TBDT) and a tightly associated cell-surface glycan-binding protein (SGBP), respectively, to form an active transport complex (Cho and Salyers, 2001; Glenwright et al, 2017; Bolam and van den Berg, 2018) ( Fig. 1A).…”
Section: Gram-negative Polysaccharide Utilization Locimentioning
confidence: 99%